Do Business Visits Cause Productivity Growth? - Massimiliano Tani; Roselyne Joyeux (Institute for the Study of Labor (IZA), 2013)
The production and diffusion of knowledge have increasingly been seen as potential causes of the observed international differences in total factor productivity and, in turn, as possible sources of economic growth. This paper presents the results of a causality study between business visits and multifactor productivity using a unique database that covers 30 sectors for 17 countries over the period 1998-2007. The results suggest that there is a causal link in some of the most innovative sectors from business visits to productivity. Business visits emerge as a fundamental channel for the spread of knowledge.
Keywords: F22; C32; C33; 330; international business travels; panel data; causality tests